2018
DOI: 10.4196/kjpp.2018.22.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition attenuates hepatic steatosis in rats with experimental Cushing's syndrome

Abstract: Cushing's syndrome (CS) is a collection of symptoms caused by prolonged exposure to excess cortisol. Chronically elevated glucocorticoid (GC) levels contribute to hepatic steatosis. We hypothesized that histone deacetylase inhibitors (HDACi) could attenuate hepatic steatosis through glucocorticoid receptor (GR) acetylation in experimental CS. To induce CS, we administered adrenocorticotropic hormone (ACTH; 40 ng/kg/day) to Sprague-Dawley rats by subcutaneous infusion with osmotic mini-pumps. We administered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
(45 reference statements)
0
6
1
Order By: Relevance
“…In addition, vorinostat ameliorated disease-induced cytotoxicity. Interestingly, in contrast to our results using vorinostat in the LAMPS model, recent reports show that vorinostat also reduced steatosis [64] and lipid metabolism pathways [65] in rat and HCC monoculture studies, respectively. These contrasting findings demonstrate the variability between animal models and simple cell culture models in assessing drug effects, highlighting the need for implementing all-human MPS model systems in drug testing platforms.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, vorinostat ameliorated disease-induced cytotoxicity. Interestingly, in contrast to our results using vorinostat in the LAMPS model, recent reports show that vorinostat also reduced steatosis [64] and lipid metabolism pathways [65] in rat and HCC monoculture studies, respectively. These contrasting findings demonstrate the variability between animal models and simple cell culture models in assessing drug effects, highlighting the need for implementing all-human MPS model systems in drug testing platforms.…”
Section: Discussioncontrasting
confidence: 99%
“…The metabolic effects of GC are mediated by intracellular GR, which translocates to the nucleus and binds to the GREs to regulate the transcription of its target genes [38]. Previous studies have reported that DEX stimulates the expression of lipogenic genes via direct GR binding at their promoters in HepG2 cells [39]. Also, long-term GC exposure induces fat accumulation in mouse adipocytes via GR-dependent miR-27b transactivation [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, inflammation during NASH development was not assessed in these models and the effect of SCFAs on liver inflammation needs further investigation. and sterol regulatory element binding protein 1c (Srebp1c) 138 . This finding provides important mechanistic insights, reviewed elsewhere 127,128 .…”
Section: [H1] Gut-derived Metabolites and Pathwaysmentioning
confidence: 99%